2008
DOI: 10.1111/j.1751-228x.2008.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Chronobiology and Sleep Habits in School and University

Abstract: ABSTRACT— Early morning school schedules are in the opposite direction to the sleep–wake cycle in adolescence and early adulthood. This conflict leads to sleep deprivation and irregular patterns whose consequences are scarcely explored. This article discusses the effects of three educational experiences with high school students, parents, teachers, and medical students. The first experience was developed with high school students in Natal, Brazil, to determine whether sleep habits would improve with increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 41 publications
6
55
2
5
Order By: Relevance
“…However, these gender differences disappear in older people. Sleep habits and chronotype scores have also been documented to differ between young men and women, with healthier sleep patterns and higher morningness scores in women than in men (Azevedo et al 2008;Roenneber et al 2007). Differences in hormonal status could be responsible for such differences, although other factors related to the lifestyle of young people may also be responsible (Roenneber et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, these gender differences disappear in older people. Sleep habits and chronotype scores have also been documented to differ between young men and women, with healthier sleep patterns and higher morningness scores in women than in men (Azevedo et al 2008;Roenneber et al 2007). Differences in hormonal status could be responsible for such differences, although other factors related to the lifestyle of young people may also be responsible (Roenneber et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
“…Most studies utilized written documentation in classrooms in combination with didactic teaching modules. [17][18][19][20][22][23][24][25][26][27][28]30 Although all studies showed improvements in sleep knowledge through these methods, many studies reported that students preferred more interactive activities rather than traditional didactic methods. 17,23,26 Indeed, Bakotić et al 21 suggest utilizing graphic designs and interactive sleep activities is more likely to promote interest in the content.…”
Section: Modes Of Deliverymentioning
confidence: 99%
See 2 more Smart Citations